Integrating renal nutrition guidelines into daily family life: a qualitative exploration. Issue 1 (1st June 2017) - Morris, A.; Love, H.; van Aar, Z.; Liles, C.; Roskell, C.
Abstract: Background: Renal dietary compliance is challenging for individuals with chronic renal disease. Advice may change depending on renal function and medical treatment. Although patients seek support from family members with these changes, no literature exists with respect to how family members experience the offering of this support. The present study aimed to describe and interpret this lived experience of family members. Methodology: Phenomenological qualitative semi‐structured interviews were conducted with 12 adult family members via telephone (transcribed verbatim). Framework analysis and the qualitative softwarenvivo, version 10 (QSR International Pty Ltd, Melbourne, VIC, Australia) were used. Participants commented on the themes for accuracy of experience representation. Results: Four major themes emerged: (i) intrusion of the renal diet; (ii) dealing with the recommendations of a renal diet; (iii) seeking a new identity; and (iv) transition of family dynamics. Perceived conflicting advice intruded into family life. Children in the family resulted in more complex nutritional decisions. Continuing a diet to avoid perceived family and wider social judgement was not an option. Balance between nurturing the family as a whole and the necessity of attending to the specific needs of one individual with renal disease was challenging. Transition to a new identity included family members being drawn to scientifically guided understandings of nutrition and a medicalisation of daily food requirements, which included low prioritisation of children's nutritional needs. Conclusion: Family members who cooked found the integration of renal nutrition guidelines challenging, with children presenting further challenges. The present study highlights the need to offer practical and psychological support to families who are coping with end‐stage renal failure and renal nutritional guidelines.